Violent peace : militarized interstate bargaining in Latin America - Mares, David R. (Columbia University Press, 2001)
-- Gabriel Marcella, U.S. Army War College.
Keywords: Latin America -- Foreign relations.; Conflict management -- Latin America.; Latin America -- Military policy.; Pacific settlement of international disputes.; Gestion des conflits -- Amérique latine.; Règlement pacifique des conflits internationaux.; Amérique latine -- Relations extérieures.; Amérique latine -- Politique militaire.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; POLITICAL SCIENCE -- International Relations -- Diplomacy.; Conflict management; Diplomatic relations; Military policy; Pacific settlement of international disputes; Latin America; Außenpolitik; Konfliktregelung; Lateinamerika; Geschichte 1900-2000.